Analisis Kualitas Sistem Pengajuan Kartu Pegawai dengan System Usability Scale dan Scrum Berbasis Web - Arief Rachman Andhika; Elfandry Bayunanda (Lembaga Pengembangan Kinerja Dosen, 2025)
XYZ is one of the official vendors of PT. Bank Rakyat Indonesia (Persero), Tbk, entrusted with the production of ID Cards or Employee Identification Cards (KTPP). Currently, the KTPP application process at the bank has been implemented through an application, but it still requires a relatively long processing time. Therefore, a web-based application was developed to accelerate the KTPP creation process. The system development was carried out using the Scrum methodology and could be completed within 72 hours or 9 working days, assuming one working day equals eight hours. To measure user satisfaction with this application, particularly among employees of PT. Bank Rakyat Indonesia (Persero), Tbk, the System Usability Scale (SUS) was employed. This method was chosen due to its efficiency, statistical validity, and its ability to provide clear, accurate evaluation scores that can be accessed online at a low cost. The SUS evaluation yielded a score of 72.0, indicating that the system is acceptable and falls within Grade B with a rating of good. These findings demonstrate that the web-based KTPP application system is feasible for implementation and can be effectively used in the KTPP application process within the relevant institution.